Punishment on Pause: Preliminary Evidence That Mindfulness Training Modifies Neural Responses in a Reactive Aggression Task - Rahrig, Hadley; Bjork, James M.; Tirado, Camila; Chester, David S.; Creswell, J. David; Lindsay, Emily K.; Penberthy, Jennifer Kim; Brown, Kirk Warren (Frontiers in Behavioral Neuroscience, 2021)
Reactive aggression, a hostile retaliatory response to perceived threat, has been attributed to failures in emotion regulation. Interventions for reactive aggression have largely focused on cognitive control training, which target top-down emotion regulation mechanisms to inhibit aggressive impulses. Recent theory suggests that mindfulness training improves emotion regulation via both top-down and bottom-up neural mechanisms and has thus been proposed as an alternative treatment for aggression. Using this framework, the current pilot study examined how mindfulness training impacts functional brain physiology in the regulation of reactive aggression. Participants were randomly assigned to two weeks of mindfulness training (n = 11) or structurally equivalent active coping training that emphasizes cognitive control (n = 12). Following training, participants underwent functional magnetic resonance imaging (fMRI) during a retaliatory aggression task, a 16-trial game in which participants could respond to provocation by choosing whether or not to retaliate in the next round. Training groups did not differ in levels of aggression displayed. However, participants assigned to mindfulness training exhibited enhanced vmPFC recruitment during punishment events (i.e., the aversive consequence of losing) relative to those receiving active coping training. Conversely, the active coping group demonstrated greater dmPFC activation when deciding how much to retaliate, in line with a bolstered top-down behavior monitoring function. The findings suggest that mindfulness and cognitive control training may regulate aggression via different neural circuits and at different temporal stages of the provocation-aggression cycle.